The The statement of the Súmula 602 from Superior Court of Justice of Brazil and the confront to the cooperative act: del 22 de febrero de 2018 y la afrenta al acto cooperativo - Ferraz Teixeira, Marianna; Ferraz Teixeira, Marília (Cooperativismo & Desarrollo, 2019)
The present investigation seeks to analyze the statement of Súmula núm. 602 of the Superior Court of Justice of Brazil, approved on February 26, 2018, where it is maintained that the Consumer Defense Code is applicable to real estate ventures promoted by a cooperative society. Since this text is applicable to similar cases that are under the jurisdiction of said court and should serve as the basis of judgment for the lower courts, it is necessary to note that the decision contravenes cooperative law and omits the peculiar characteristics between housing cooperatives and its partners, forcibly qualifying this relationship as consumption. Hence, it is necessary to inquire into the specificity of cooperative law to distinguish the special relationship that exists between cooperatives and their partners; thus, evidence of the misunderstanding and prejudice that the jurisprudential decision referred to will have in the future for cooperative housing societies. It is also necessary to review the rules of the civil process and the Internal Regulation of the Superior Court of Justice to verify the possibility of altering this negative case-law sitting with respect to housing cooperatives.